What happens structurally and chemically during sodium uptake and release by Ni2P2S6: a combined X-ray diffraction, X-ray absorption, pair distribution function and MAS NMR analysis. Issue 42 (26th October 2020) - van Dinter, Jonas; Synnatschke, Kevin; Engesser, Tobias A.; Indris, Sylvio; Wolff, Niklas; Gronenberg, Ole; Etter, Martin; Cibin, Giannantonio; Kienle, Lorenz; Backes, Claudia; Bensch, Wolfgang
Abstract : The layered compound Ni2 P2 S6 was electrochemically characterized for application as an anode material in sodium-ion batteries (SIBs) and the corresponding reaction mechanism was investigated via a multi-method approach. Abstract : The layered compound Ni2 P2 S6 was electrochemically characterized for application as an anode material in sodium-ion batteries (SIBs). A high reversible capacity of 621 mA h g −1 at 1 A g −1 was achieved after 190 cycles. The investigation of the complex reaction mechanism of the conversion reaction was performed applying complementary techniques including X-ray powder diffraction, pair distribution function analysis, X-ray absorption spectroscopy, 19 F/ 23 Na/ 31 P MAS NMR, TEM and nano-EDX. The results highlight that Na uptake for up to 5 Na per formula unit (f.u.) led to reduction of Ni 2+ to metallic Ni nanoparticles and concomitant formation of an intermediate compound Na4 P2 S6 . Increasing the Na content to 12 Na per f.u. generates nanocrystalline Na2 S, which is accompanied by the loss of the long-range order of the pristine sample. In the completely discharged state elemental Ni and Na2 S are present, but in contrast to literature reports, no evidence for the formation of Na x P phases was found. During the charge process, Ni3 S2 is formed upon the release of ∼11.7 Na per f.u.